The microstructure evolution and precipitation behavior of TiB2/Inconel 718 composites manufactured by selective laser melting. (July 2022) - Zheng, Yongsheng; Liu, Fenggang; Zhang, Wenjun; Liu, Fencheng; Huang, Chunping; Gao, Jiaying; Li, Qiuge
Abstract: Additive Manufacturing is an advanced material processing technology emerging in recent years. However, coarse columnar grain structure of additive manufactured metals reduces the performance of the material. Facilitating the columnar to equiaxed transition (CET) has become a research hotspot. In this paper, the equiaxed grain of additive manufactured Inconel 718 was achieved by adding TiB2 particles. Simultaneously, the microstructure evolution and precipitation behavior with nano-TiB2 particles addition were studied. The results show that the grain morphology of Inconel 718 exhibited coarse columnar grains with epitaxial growth and strong <100> texture. When 3 wt% TiB2 was added, the columnar grains became finer, further increased the content of TiB2 to 5 wt%, the equiaxed grains were obtained and the texture intensity decreased significantly. In addition, TiB2 partially melted under the high laser energy changed the phase precipitation behavior of Inconel 718 from chain-like Laves phase to reticulated (γ + M3 B2 ) eutectics, which lead to the hardness increased from 276 HV to 578 HV when 5 wt% TiB2 was added. After heat treatment, the precipitation of high density γ′ and γ″ strengthening phase were promoted the hardness increased by 87% to 516 HV in Inconel 718. However, the hardness of TiB2 reinforced samples showed a little change, which could be attributed to the partial dissolution of M3 B2 boride during the heat treatment.